Guinness world records, 2001 - Guinness World Records Ltd. (London) (London Guinness World Records Ltd, 2001)
Guinness world records, 2001, a complete new edition including the first records of the new millennium from strength to strength in all areas. This book offers plenty to fescinate, stimulate, amaze, amuse, revolt and inspire you.
Keywords: World records